The Custodians of the Gift Fairy Beliefs, Holy Doubts and Heritage Paradoxes on a Fijian Island - Pigliasco, Guido (Strumenti per la didattica e la ricerca, 2020)
Emerging from more than two decades of research in the field and in the archives, the essays collected here explore the multifaceted topic of the Fijian firewalking ceremony, the vilavilairevo. The collection examines the intersection of the intertwined topics of cultural property, reproduction of tradition, and change with issues of (post)colonial representation, authenticity, and ethnic identity. The essays advance new insights on the tourist gaze and the safeguarding of intangible cultural heritage and pose serious questions regarding the role of digital and social media as tools for preserving cultural legacies and extending traditional cultural worlds into new domains. Focusing on the response of the Sawau tribe of the island of Beqa to the commodification of the vilavilairevo as their iconic practice, this essay collection ultimately illuminates how the Christian cultural dynamics and unprecedented dogmatic schism surrounding the vilavilairevo spectacle are reshaping local notions of heritage, social sentiment, and social capital.